Assessment of Knowledge, Attitude and Practice Towards Infection Prevention and Control Among Health Staff at Seiyun General Hospital Authority - Sarah O. Alsawmhi; Anwar S. Alhussan; Hassan Pyar; Taher I. Bin Sumait (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Healthcare workers (HCWs) are continuously exposed to pathogenic microorganisms, which can lead to serious infections. Infection prevention and control (IPC) relies heavily on HCWs’ knowledge, attitudes, and practices (KAP). This study aimed to assess KAP towards IPC among health staff at Seiyun General Hospital Authority, Yemen, during 2023–2024. A cross-sectional study was conducted involving 106 participants. Data were collected through a self-administered questionnaire and analyzed using SPSS software. Among participants, 60.6% held a diploma, 62.5% were male, 37.5% were nurses, and 33.7% had 1–5 years of experience. Regarding knowledge, 91.3% reported understanding IPC, and 76.9% acknowledged the role of sterilization. In terms of attitude, 60% strongly agreed that handwashing reduces infections. As for practices, 90.4% washed their hands before patient care, and 76% educated patients about IPC. Significant associations were found between KAP levels and education, age, gender, job category, and experience. Occupational category and work experience influenced KAP levels, while education, age, and gender showed limited impact.